2016
DOI: 10.1101/088732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromatin accessibility dynamics reveal novel functional enhancers inC. elegans

Abstract: Chromatin accessibility, a crucial component of genome regulation, has primarily been studied in homogeneous and simple systems, such as isolated cell populations or early-development models. Whether chromatin accessibility can be assessed in complex, dynamic systems in vivo with high sensitivity remains largely unexplored. In this study, we use ATAC-seq to identify chromatin accessibility changes in a whole animal, the model organism Caenorhabditis elegans, from embryogenesis to adulthood. Chromatin accessibi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 86 publications
6
71
0
Order By: Relevance
“…hypodermal, muscle, neuronal) which proliferate after hatching (Sulston and Horvitz 1977). However, the select inactivation of highly-transcribed early gene promoters would lead to an expected decrease in nascent RNA levels (Tome et al 2018)-instead, we find consistent nascent RNA transcription, a readout shown to positively correlate with chromatin accessibility at multiple stages of C. elegans development (Daugherty et al 2017).…”
Section: Operons Pervasive Transcription and Post-transcriptional Mmentioning
confidence: 59%
See 4 more Smart Citations
“…hypodermal, muscle, neuronal) which proliferate after hatching (Sulston and Horvitz 1977). However, the select inactivation of highly-transcribed early gene promoters would lead to an expected decrease in nascent RNA levels (Tome et al 2018)-instead, we find consistent nascent RNA transcription, a readout shown to positively correlate with chromatin accessibility at multiple stages of C. elegans development (Daugherty et al 2017).…”
Section: Operons Pervasive Transcription and Post-transcriptional Mmentioning
confidence: 59%
“…In addition, we considered the possibility that the stable H3K27ac and H3K4me2 ChIP-seq profiles generated from synchronized embryos may be disproportionately biased by the crosslinking and immunoprecipitation procedure (Teytelman et al 2013). We compared embryo H3K27ac peak positions relative to accessible chromatin sites identified by a cross-linking independent assay, ATAC-seq (Daugherty et al 2017). We found that the vast majority of transposase accessible sites identified in a mixed population of embryos to directly overlap (~60%), or lie within 5 kb (~70%) of our early embryo H3K27ac peaks ( Figure 1C).…”
Section: Stable Maintenance Of Pol II Associated Histone Modificationmentioning
confidence: 99%
See 3 more Smart Citations